The Principal’s Role in Motivating Teachers to Improve Their Pedagogical Competence Through Information Technology - Putra, Budhi Andi; Raharja, Setya (Journal of Educational Sciences, 2025)
This study analyzes the role of school principals in enhancing teachers' pedagogical competencies through the use of Information Technology (IT) in public elementary schools in Bukit Batu District. The main focus is on how principals motivate teachers and integrate IT to improve the quality of pedagogical competencies. A qualitative phenomenological approach was used to explore the experiences of principals and teachers related to motivation and the strengthening of competencies through IT. Data were collected through in-depth interviews, participatory observation, and document studies at SD Negeri 005 and SD Negeri 009 in Bukit Batu during the period from May to November 2025. The findings show that principals play a crucial role in enhancing pedagogical competencies through IT, such as initiating training and mentoring. However, challenges such as limited devices, unstable internet access, and teachers' readiness remain major obstacles. Supporting factors include regular training and support from the Education Office, while the main barriers are limited IT facilities, varied teacher skills, and differing motivation levels. To optimize the use of IT, improvements in facilities, more intensive training, and adequate technical support are needed.